Assessment of the Effectiveness of a Pilates Program on Physical Fitness Among Adolescent Students in School - Kaouri , Ifigeneia; Argiriadou, Eirini; Katartzi , Ermioni; Praskidou, Anastasia-Kassiani; Vrabas, Ioannis; Mavrovouniotis, Fotios (Alberta Journal of Educational Research, 2024)
The purpose of the present study was to examine the effectiveness of a Pilates program in the context of the physical education course at school, on aerobic capacity, muscular strength, muscular endurance, and flexibility of high school students. The voluntary participants were 42 high school students, aged 15 to 17 years, randomly divided into a Pilates group (PG; n = 24) that were taught and practiced Pilates exercises and a control group (CG; n = 18) that participated in the regular physical education school program, during physical education course at school, twice a week, for 45 minutes, for 10 weeks. After the 10-week period, PG significantly improved in all physical fitness parameters, while CG only in muscular endurance. The results demonstrated the very positive effects of the Pilates program as an alternative form of physical activity during the physical education course at school, on physical fitness parameters of high school students. Keywords: aerobic capacity, muscular strength, muscular endurance, flexibility. Le but de cette étude était d'examiner l'efficacité de l’entrainement base sur des exercices “Pilâtes” dans le cadre d’un cours d'Éducation Physique à l'école, sur la capacité aérobie, la force musculaire, l'endurance musculaire et la flexibilité des élèves de la classe secondaire. Les participants volontaires étaient 42 élèves du secondaire, âgés de 15 à 17 ans, répartis au hasard en un groupe Pilates (PG ; n = 24) qui a appris et pratiqué des exercices de Pilates, et un groupe témoin (CG ; n = 18) qui a participé au programme scolaire régulier d'éducation physique, pendant le cours d'éducation physique à l'école, deux fois par semaine, pendant 45 minutes, pendant 10 semaines. Après la période de 10 semaines, le PG s’est amélioré de manière significative dans tous les paramètres de condition physique, tandis que le CG n’a amélioré que l’endurance musculaire. Les résultats ont démontré les effets très positifs du programme Pilâtes, comme forme alternative d'activité physique à l'école, sur les paramètres de condition physique des élèves du secondaire. Mots clés : capacité aérobie, force musculaire, endurance musculaire, flexibilité.